KAJIAN MUTU KIMIAWI IKAN CAKALANG (Katsuwonus pelamis L.) ASAP (FUFU) SELAMA PENYIMPANAN SUHU RUANG DAN SUHU DINGIN - Wally, Erni; Mentang, Feny; Montolalu, Roike Iwan (Sam Ratulangi University, 2015)
Fish as a functional food plays an important role for health and preventing diseases. The objective of the study was to difermined the quality of smoked Skipjack (Katsuwonus pelamis L.) found from the traditional market in Bahu Manado. The method of the study was to analyzet the TVB-N by using Conway, pH by using pH meters and water contents by using oven method. The product was storage at 40C and 27-280C ( refrigeratot and room temperature) for 4 days, data were analyzet using statistical test from the triplicate analyzet. The results obtained, the TVB-N value of smoked Skipjack (Katsuwonus pelamis L.) at 0 day storage in 27-280C (A1B1) and refrigerator 40C (A1B2) was 11,2 mg/100gr, 2 days storage 27-280C (A2B1) is 44,8 mg/100gr and 40C (A2B2) is 19,6 mg/100gr, and 4 days storage in 27-280C (A3B1) is 56 mg/100gr and 40C (A3B2) is 28 mg/100gr. The pH value storage at 40C was 5,7 and no differents among the sample, in contrast at 27-280C value varied from 5,7 to 6,3 and 6,6. The water contents storage at 27-280C were at 0 day (A1B1) is 62,5%, 2 days (A2B1) is 62,8% and 4 days (A3B1) is 63,8% and storage 40C were 0 day (A1B2) is 59%, 2 days (A2B2) is 61,1% and 4 days (A3B2) is 62,7%. Based on the results of the TVB-N value, pH and water contents of smiked Skipjack (Katsuwonus pelamis L.) found from the traditional market at Bahu Manado were acceptable until 4 days storage. While the smoked Skipjack (Katsuwonus pelamis L.) storage at 27-280C (room temperature) acceptable until 2 days storage. Â Keywords: Skipjack (Katsuwonus pelamis L.), Smoke, Study Quality, Chemical, TVB-N, pH, Moisture.